1984
DOI: 10.1021/bi00301a046
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism-based inactivation of mitochondrial monoamine oxidase by N-(1-methylcyclopropyl)benzylamine

Abstract: Three different radioactively labeled N-(1-methylcyclopropyl)benzylamines [N-(1-Me)CBA] were synthesized and used to show which atoms of the inactivator remain bound to monoamine oxidase (MAO) after inactivation. Organic chemical reactions were employed to elucidate the structure of the enzyme adduct and clarify the mechanism of inactivation. Following inactivation and dialysis, the benzyl substituent is lost, but the methyl group and cyclopropyl carbons remain attached to the enzyme even after further dialysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
43
0

Year Published

1985
1985
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 36 publications
4
43
0
Order By: Relevance
“…In contrast, the Miller and Edmondson study also found that this effect on the reaction rate is much less effective in the case of MAO B than in that of MAO A, opening up the possibility that the two isozymes do not function by the same mechanism. On the other hand, such different behaviour in MAO isozymes is in accordance with the radical mechanism proposed by Silverman and co-workers [40][41][42][43][44] in which the first step is the one-electron transfer from the substrate amino group to the flavin to form the substrate radical cation. However, subsequent experiments by Edmondson et al, [23,45] as well as related electron paramagnetic resonance (EPR) studies [46] and stopped-flow kinetic determinations, [47,48] failed to provide evidence for any radical intermediates.…”
Section: Introductionsupporting
confidence: 88%
“…In contrast, the Miller and Edmondson study also found that this effect on the reaction rate is much less effective in the case of MAO B than in that of MAO A, opening up the possibility that the two isozymes do not function by the same mechanism. On the other hand, such different behaviour in MAO isozymes is in accordance with the radical mechanism proposed by Silverman and co-workers [40][41][42][43][44] in which the first step is the one-electron transfer from the substrate amino group to the flavin to form the substrate radical cation. However, subsequent experiments by Edmondson et al, [23,45] as well as related electron paramagnetic resonance (EPR) studies [46] and stopped-flow kinetic determinations, [47,48] failed to provide evidence for any radical intermediates.…”
Section: Introductionsupporting
confidence: 88%
“…22) in a concentration-and time-dependent manner. The concentration required for 50% inhibition after 15 min in aerobic solution was 0.25 M. The inhibition was fully reversible by dilution.…”
Section: Resultsmentioning
confidence: 99%
“…5, path a only, R-H, R1=CH3). 259,260 Inactivation of MA0 by N-cyclopropyl-a-methylbenzylamine was suggested to lead almost exclusively to the formation of a labile adduct with a residue other than the flavin (Fig. 5, path a, R=CH3, R1=H).…”
Section: Cyclopropylamine Derivativesmentioning
confidence: 99%